Plant-Based Milk As An Alternative To Dairy Milk - The Challenges And Way Forward - Rashid, Nor Syahirah Abd (Universiti Sains Malaysia, 2020)
This literature review aims to discuss the technological constraint faced during the processing of plant-based milk and to review the nutritional properties, sensory acceptability, stability, functional and application challenges of plant-based milk. Plant-based milk can be defined as a liquid that has a particle size distribution of 5-10μm resulted from the breakdown of plant material and homogenization process. Plant-based milk can be made from cereal, legume, seed, nut and pseudo-cereal. The examples of plant-based milk are oats milk, soymilk, almond milk, rice milk, coconut milk, peanut milk and sesame milk. While dairy milk has already well accepted by consumer, plant-based milk still faces challenges to grow in the market. Plant-based milk has problem related to elimination of anti-nutrient factors and limitations of heat treatment applied in the processing. The conventional heating is unable to eliminate all the undesirable compounds. The nutritional properties of plant-based milk are not comparable to dairy milk without fortification and quality of protein of plant-based is lower than dairy milk in terms of amino acids array. The issue of sensory properties for plant-based milk is basically caused by beany flavour due to the presence of some undesirable compounds such as lipoxygenase, hexanal and isoflavones. Besides, plant-based milk normally made up of big particles such as protein and carbohydrate that leads to phase separation on storage. This can be solved by the addition of gums but the right type and amount of gums should be carefully decided to prevent unnecessary interaction with compounds naturally present in the product.